2021
DOI: 10.1097/aud.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Self-reported Hearing Disability in Adults With Normal Hearing

Abstract: Objectives: Despite a diagnosis of normal hearing, many people experience hearing disability (HD) in their everyday lives. This study assessed the ability of a number of demographic and auditory variables to explain and predict self-reported HD in people regarded as audiologically healthy via audiometric thresholds.Design: One-hundred eleven adults (ages 19 to 74) with clinically normal hearing (i.e., audiometric thresholds ≤25 dB HL at all octave and interoctave frequencies between 0.25 and 8 kHz and bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…However, these effects did not survive correction for multiple comparisons. This trend of poorer self-reported hearing function among workers is similar to that reported by Kamerer et al (2022) , who found that greater history of impulsive noise exposure (e.g., explosion or firearm) significantly predicted lower SSQ12 scores in audiometrically normal adults ( n = 111) aged 19–74 years. Similarly, Worede et al (2022) who surveyed a group of metal and wood Ethiopian workers with exposure to unsafe levels of occupational noise found that about 20.7% of these workers believe they may have a hearing impairment.…”
Section: Discussionsupporting
confidence: 87%
“…However, these effects did not survive correction for multiple comparisons. This trend of poorer self-reported hearing function among workers is similar to that reported by Kamerer et al (2022) , who found that greater history of impulsive noise exposure (e.g., explosion or firearm) significantly predicted lower SSQ12 scores in audiometrically normal adults ( n = 111) aged 19–74 years. Similarly, Worede et al (2022) who surveyed a group of metal and wood Ethiopian workers with exposure to unsafe levels of occupational noise found that about 20.7% of these workers believe they may have a hearing impairment.…”
Section: Discussionsupporting
confidence: 87%
“…For example, individuals with a normal HFPTA may still have some degree of hearing loss, particularly above 4 kHz. Notably, reduced hearing in the ultra-high frequencies (thresholds 8 kHz or higher) has been related to worse speech-in-noise abilities ( Hunter et al 2020 ; Polspoel et al 2022 ), and lower scores on the SSQ12 ( Kamerer et al 2022 ). On a closely related note, individuals who have normal hearing, but have a history of noise exposure were also more likely to report lower SSQ12 values ( Kamerer et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, reduced hearing in the ultra-high frequencies (thresholds 8 kHz or higher) has been related to worse speech-in-noise abilities ( Hunter et al 2020 ; Polspoel et al 2022 ), and lower scores on the SSQ12 ( Kamerer et al 2022 ). On a closely related note, individuals who have normal hearing, but have a history of noise exposure were also more likely to report lower SSQ12 values ( Kamerer et al 2022 ). Taken together, these data are consistent with the idea that a normal HFPTA may not indicate completely normal hearing, particularly above 8 kHz, and that hearing loss in those regions can be associated with poorer speech-in-noise abilities and SSQ12-Speech5 scores.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with very detailed characterization of hearing, 20.2% of the subjects with selfreported hearing loss did not even meet the definition of mild hearing loss in the pure-tone audiogram while 6.2% of the individuals reporting no hearing problem did have at least mild hearing loss in audiometry (Gates et al 1990). It seems, however, possible that self-reported hearing loss is sensitive for hearing impairment that does not yet yield pathological results in pure-tone audiometry or other diagnostic tests (Kamerer et al 2022). This suggests that self-reported hearing represents a different spectrum of auditory function and potentially central processing in contrast to pure-tone audiometry.…”
Section: Discussionmentioning
confidence: 99%